2012
DOI: 10.1111/j.1530-0277.2012.01782.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effect of the GABAB Receptor Agonist, Baclofen, and the Positive Allosteric Modulator of the GABAB Receptor, GS39783, on Alcohol Self‐Administration in 3 Different Lines of Alcohol‐Preferring Rats

Abstract: Background Administration of the GABAB receptor agonist, baclofen, and positive allosteric modulator (PAM), GS39783, has been repeatedly reported to suppress multiple alcohol-related behaviors, including operant oral alcohol self-administration, in rats. The present study was designed to compare the effect of baclofen and GS39783 on alcohol self-administration in three lines of selectively bred, alcohol-preferring rats: Indiana alcohol-preferring (P), Sardinian alcohol-preferring (sP), and Alko Alcohol (AA). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
44
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 73 publications
(48 citation statements)
references
References 100 publications
4
44
0
Order By: Relevance
“…Different typologies of patients display a varying response to medication [165,166]. Interestingly, a preclinical study found that different lines of alcohol-preferring rats vary in their sensitivity to treatment with baclofen [98]. It has been proposed that one of the main reasons for the divergent results collected by RCTs on AUDs may be the different typologies of patients recruited in these studies [119].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different typologies of patients display a varying response to medication [165,166]. Interestingly, a preclinical study found that different lines of alcohol-preferring rats vary in their sensitivity to treatment with baclofen [98]. It has been proposed that one of the main reasons for the divergent results collected by RCTs on AUDs may be the different typologies of patients recruited in these studies [119].…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, treatment with baclofen has been reported to suppress the following: (1) alcohol drinking in rats exposed to the standard, home cage 2-bottle ‘alcohol versus water' choice regimen (a validated animal model of excessive alcohol consumption in humans) [29,85,86,87,88]; (2) relapse-like drinking in previously abstinent rats [89,90]; (3) alcohol reinforcing and motivational properties in rats, mice and nonhuman primates trained to perform a given amount of ‘work' (usually responding on a lever) to gain access to the alcohol solution [91,92,93,94,95,96,97,98,99]; (4) reinstatement of alcohol-seeking behavior triggered in rats by the noncontingent presentation of a complex of cues previously associated with alcohol availability [100]; (5) alcohol-induced conditioned place preference (CPP; index of alcohol rewarding properties) in mice [101], and (6) alcohol-induced stimulation of locomotor activity in rats and mice (index of alcohol euphorigenic properties) [102,103,104,105]. …”
Section: Baclofen and Sudsmentioning
confidence: 99%
“…In addition, they reduce self-administration of alcohol (Orru et al, 2005(Orru et al, , 2012Liang et al, 2006;Maccioni et al, 2007Maccioni et al, , 2008Maccioni et al, , 2009Maccioni et al, , 2010aMaccioni et al, , b, 2012Agabio et al, 2012), cocaine , and nicotine (Mombereau et al, 2007;Paterson et al, 2008;Vlachou et al, 2011). GABA B receptorpositive modulators are thought to have advantages as potential medications for anxiety, depression, and drug addiction, because they may have a better side-effect profile than GABA B receptor agonists, based on the notion that selective enhancement of activated receptors has effects that differ from indiscriminate activation of all receptors.…”
Section: Introductionmentioning
confidence: 99%
“…The activation of these receptors with the GABA B receptor agonist baclofen inhibits dopaminergic neurons indirectly and directly [7]. The importance of the GABA B receptor in the reinforcing and motivational properties of alcohol was confirmed [8].…”
Section: Introductionmentioning
confidence: 74%